Progress and Prospects of CRISPR/Cas Systems in Insects and Other Arthropods - Sun, Dan; Guo, Zhaojiang; Liu, Yong; Zhang, Youjun (Frontiers in Physiology, 2017)
Clustered regularly interspaced short palindromic repeats (CRISPR) and the CRISPR-associated gene Cas9 represent an invaluable system for the precise editing of genes in diverse species. The CRISPR/Cas9 system is an adaptive mechanism that enables bacteria and archaeal species to resist invading viruses and phages or plasmids. Compared with zinc finger nucleases and transcription activator-like effector nucleases, the CRISPR/Cas9 system has the advantage of requiring less time and effort. This efficient technology has been used in many species, including diverse arthropods that are relevant to agriculture, forestry, fisheries and public health; however, there is no review that systematically summarizes its successful application in the editing of both insect and non-insect arthropod genomes. Thus, this paper seeks to provide a comprehensive and impartial overview of the progress of the CRISPR/Cas9 system in different arthropods, reviewing not only fundamental studies related to gene function exploration and experimental optimization but also applied studies in areas such as insect modification and pest control. In addition, we also describe the latest research advances regarding two novel CRISPR/Cas systems (CRISPR/Cpf1 and CRISPR/C2c2) and discuss their future prospects for becoming crucial technologies in arthropods.